Analyzing Factors that Affect the Blitar Society Religiosity as the Impact of Wayang Wali Shows Based on Structural Equation Modelling Approaches - Sari, Adma Novita; Widyangga, Pressylia Aluisina Putri; Romadhoni, M. Suma Firman; Yusuf, Bima Sakti Putra; Mardianto, M. Fariz Fadillah (ESTIMASI: Journal of Statistics and Its Application, 2025)
This research analyzes the impact of Wayang Wali performances on the religiosity of the Blitar society. Data was collected through a survey with stratified random sampling technique to 367 people in Blitar. The study employs two approaches: Confirmatory Factor Analysis (CFA) and Structural Equation Modeling-Partial Least Squares (SEM-PLS). CFA analysis show that all indicators for the five latent variables have shown significant Z-values, exceeding the threshold of 1.96. This confirms that the indicators are reliable measures for their respective latent constructs. Given this significance, the model demonstrates robust construct validity, ensuring that each latent variable is accurately represented by its indicators. From inner and outer models analysis, show that family environment, personality, social piety, and transpersonal psychology have an effect on the religiosity of the Blitar community because the t-statistical value > t table or 1.96 and the P-Value is 0.000 < 0.05. Through this research, Blitar government can enhance community religiosity, preserving cultural heritage and strengthening religious and moral values.